(untitled) (Al-Academy, 2017)
The Main think that be kept by the speech communication as a concept traditionally being expressed on the subject or a certain idea of ​​a goal came on as needed functional addressed to recipients of benefits or likely to benefit from those rhetorical message through a speech importance and priority of the effect of not less than the effect of that letter, in science content role ends once you absorb it mentally, either in the art of design Valamadmon intellectual embodied through its interaction with the overall shape of the finished design, and often content is associated in the mind of the receiver through a letter communicative linked to the sense or the goal that meant the designer, and try to identify and explain. And meaning in content in, as long as the figure captures particles intellectual content at the technical level, it is imperative that the artist not interfere in the context of directing a certain point, but he has to leave the artwork poses itself in accordance with the logical sequence and dramatic cohesion between particles secured, came the idea of ​​this research by identifying the research problem by asking the following: how to enhance the shape speech communication of the place, as well as determine the terms of the speech, communication, form and content and commercial advertising, which included the second chapter on the concept of speech and its implications, the form and content conceptual, recognize the shape visually, Advertising trade, and included the third quarter results that came from: the transformation of the track (technical) as a result of scientific technological development has given a recipe for breeding and the emergence of new patterns of speech communication to crystallize shape and strengthen the communication of the message.